2003
DOI: 10.1167/iovs.02-0664
|View full text |Cite
|
Sign up to set email alerts
|

Expression and Localization of Tenomodulin, a Transmembrane Type Chondromodulin-I-Related Angiogenesis Inhibitor, in Mouse Eyes

Abstract: These results indicate a potential role for TeM in prevention of vascular invasion in the mouse eye and the possibility of both TeM and ChM-I as candidates for use in gene therapy approaches to treatment of ocular angiogenesis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
74
0
3

Year Published

2004
2004
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 65 publications
(83 citation statements)
references
References 38 publications
6
74
0
3
Order By: Relevance
“…Figure 6 shows the effects of IGF-1 deficiency and hypertension on the hippocampal expression of the angiogenesis inhibitors Serpinf1 (PEDF), f i b u l i n -5 ( F b l n 5 ) ( S u l l i v a n e t a l . 2 0 0 7 ) , thromhospondin-1 (Thbs1) (Lawler 2002), Thbs2 (Volpert et al 1995), the potent anti-angiogenic chemokine platelet factor 4 (Pf4) (Bikfalvi 2004); vasohibin-1 (Vash1), which is a newly recognized (Takano et al 2014), Adamts1 ("a disintegrin and metalloproteinase with thrombospondin motifs 1"), which inhibits angiogenesis (Lee et al 2006) by suppressing endothelial cell proliferation; Col18a1, whose expression level impacts endostatin signaling and endothelial angiogenic capacity (Li and Olsen 2004) (endostatin, a potent inhibitor of angiogenesis, is a 20-kDa C-terminal fragment derived from type XVIII collagen); semaphorin-3F (Sema3f) (Ungvari et al 2011b;Frisbee et al 2007); tenomodulin (Tnmd) (Oshima et al 2003); brainspecific angiogenesis inhibitor 1 (Bai1; also known as adhesion G protein-coupled receptor B1 [ADGRB1]) (Nishimori et al 1997); chromogranin A (Chga), which encodes the precursor to several angiogenesis inhibitor peptides including vasostatin-1 and vasostatin-2 (Helle and Corti 2015) and maspin ("mammary serine protease inhibitor"; encoded by the Serpinb5 gene (Qin and Zhang 2010). Figure 7 shows the expression of Tnfa, whose overproduction has been causally linked to microvascular rarefaction (Frisbee et al 2014); Tgfb1, which regulates multiple aspects of the angiogenic process and contributes to hypertension-induced microvascular rarefaction in the heart (Koitabashi et al 2011); Tgfa; angiogenin (Ang, also known as ribonuclease 5), which is a potent stimulator of angiogenesis and an inhibitor of endothelial apoptosis; Edil3 (EGF-like repeats and discoidin Ilike domains 3), which encodes a glycoprotein secreted by endothelial cells that regulates apoptosis, cell migration (Zhong et al 2003) and induces cerebral angiogenesis in mice (Fan et al 2008); midkine (Mdk, also known as neurite growth-promoting factor 2 or NEGF2), which is a pleiotropic growth factor regulating cell proliferation, cell migration and promoting angiogenesis (Mashour et al 2001 [HB-GAM]), which is a pro-angiogenic growth factor that is structurally related to midkine and whose expression in the adult brain is induced by ischemia; Tymp (thymidine phosphorylase, also known as platelet-derived endothelial cell growth factor [ECGF1], which stimulates endothelial cell proliferation and induces angiogenesis in the brain …”
Section: Igf-1 Deficiency Exacerbates Hypertension-induced Cerebromicmentioning
confidence: 99%
“…Figure 6 shows the effects of IGF-1 deficiency and hypertension on the hippocampal expression of the angiogenesis inhibitors Serpinf1 (PEDF), f i b u l i n -5 ( F b l n 5 ) ( S u l l i v a n e t a l . 2 0 0 7 ) , thromhospondin-1 (Thbs1) (Lawler 2002), Thbs2 (Volpert et al 1995), the potent anti-angiogenic chemokine platelet factor 4 (Pf4) (Bikfalvi 2004); vasohibin-1 (Vash1), which is a newly recognized (Takano et al 2014), Adamts1 ("a disintegrin and metalloproteinase with thrombospondin motifs 1"), which inhibits angiogenesis (Lee et al 2006) by suppressing endothelial cell proliferation; Col18a1, whose expression level impacts endostatin signaling and endothelial angiogenic capacity (Li and Olsen 2004) (endostatin, a potent inhibitor of angiogenesis, is a 20-kDa C-terminal fragment derived from type XVIII collagen); semaphorin-3F (Sema3f) (Ungvari et al 2011b;Frisbee et al 2007); tenomodulin (Tnmd) (Oshima et al 2003); brainspecific angiogenesis inhibitor 1 (Bai1; also known as adhesion G protein-coupled receptor B1 [ADGRB1]) (Nishimori et al 1997); chromogranin A (Chga), which encodes the precursor to several angiogenesis inhibitor peptides including vasostatin-1 and vasostatin-2 (Helle and Corti 2015) and maspin ("mammary serine protease inhibitor"; encoded by the Serpinb5 gene (Qin and Zhang 2010). Figure 7 shows the expression of Tnfa, whose overproduction has been causally linked to microvascular rarefaction (Frisbee et al 2014); Tgfb1, which regulates multiple aspects of the angiogenic process and contributes to hypertension-induced microvascular rarefaction in the heart (Koitabashi et al 2011); Tgfa; angiogenin (Ang, also known as ribonuclease 5), which is a potent stimulator of angiogenesis and an inhibitor of endothelial apoptosis; Edil3 (EGF-like repeats and discoidin Ilike domains 3), which encodes a glycoprotein secreted by endothelial cells that regulates apoptosis, cell migration (Zhong et al 2003) and induces cerebral angiogenesis in mice (Fan et al 2008); midkine (Mdk, also known as neurite growth-promoting factor 2 or NEGF2), which is a pleiotropic growth factor regulating cell proliferation, cell migration and promoting angiogenesis (Mashour et al 2001 [HB-GAM]), which is a pro-angiogenic growth factor that is structurally related to midkine and whose expression in the adult brain is induced by ischemia; Tymp (thymidine phosphorylase, also known as platelet-derived endothelial cell growth factor [ECGF1], which stimulates endothelial cell proliferation and induces angiogenesis in the brain …”
Section: Igf-1 Deficiency Exacerbates Hypertension-induced Cerebromicmentioning
confidence: 99%
“…4 It has been shown that the TNMD protein can have different forms. 3,5,7,12 For example, TNMD has been detected as N-glycosylated and non-Nglycosylated form with molecular mass of 45 and 40 kDa, respectively. 3 The same forms are found in pigs, namely in pigs' chordae tendineae cordis (CTC) and pigs' eye.…”
Section: Protein Structure and Locationmentioning
confidence: 99%
“…12 These forms have been also found in mice. 5,7 More specifi cally, a 16-kDa secreted form cleaved in a tissue-specifi c manner has been detected in the porcine CTC, but not in the eye. N-terminal part of the protein has been presented in the CTC, as well.…”
Section: Protein Structure and Locationmentioning
confidence: 99%
See 2 more Smart Citations